PENGARUH UKURAN PARTIKEL DAN LAMA EKSTRAKSI TERHADAP KARAKTERISTIK EKSTRAK WARNA ALAMI BUAH PANDAN (Pandanus tectorius) - Oka Antari, Ni Made Ria; Wartini, Ni Made; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 4 (2015): Desember)
This aims of this study were to 1) know  the  effect  of particle size and extraction time on the characteristics of  pandanus fruit  extract  natural dyes, 2) obtain particle size and extraction time to produce pandanus fruit extract natural dyes with the best characteristics.This study used  a  factorial  randomized block design. The first factor  is  the size of the particle consists of two levels :  40 and 60 mesh. The second factor is a extraction  time  consists of three levels :  3, 5 and 7 hours. The experiments are grouped into 3 groups based on the time of implementation, in order to obtain 18 units  experiment. Variables observed that the yield, total carotenoid content, color intensity, color score, and the level of color strength.The results showed that the particle  size effect on yield, total carotenoids  content, balanced color and color strength.  Extraction time affect  on the extraction yield, the level of brightness (L*), the  level  of redness (a*), the level of yellow (b*), a score of color and color strength. The interaction of particle size and extraction time affect on total carotenoids  content, the level of redness (a*), but does not affect the yield, the level of brightness (L*) and the level of yellow (b*). The particle size of 60 mesh  and  5  hour  extraction  time  produce  extract natural dyes  fruit in best with the following characteristics: yield of 4,80%, total carotenoid content of 0,242%, the  level of brightness (L*) of 6,29, the level of redness (a*) -3,70, the level of yellow (b*) 28,93, a score of 4,0 color (red) and strength of color is 6,0 (the most powerful).
Keywords: 70,